The seated inactivity trial (S.I.T.): physical activity and dietary outcomes associated with eight weeks of imposed sedentary behavior - Cull, Brooke J. (Kansas State University, 2014)
Background: Time spent in sedentary behaviors, independent of physical activity levels, is a risk factor for chronic diseases and all-cause mortality. It is unknown whether physically active adults alter their dietary and/or physical activity behaviors in response to imposed sedentary time. The aim of this study was to determine whether imposing 10 hours of sedentary time per week for 8 weeks would alter physical activity and/or dietary profiles of physically active adults. Methods: Sixteen physically active, healthy young adults were randomized into either the no-intervention control (CON) group (n=8) or the sedentary-intervention (SIT) group (n=8). SIT participants attended monitored sedentary sessions for 10 hours per week (4 days; 2.5 hours) for 8 weeks. Assessments occurred at baseline, and weeks 4 and 8. Dietary information was collected through 3-day food records and physical activity was assessed through 7 days of accelerometry (Actical at the wrist). Results: There were no differences in physical activity profiles in SIT or CON groups when baseline and week-8 average (average weeks) were compared to the week-4 assessment. Differences in step counts comparing the average weeks and week 4 were not significantly different between CON and SIT groups (CON = 615.1 ± 3019.1, SIT= -1158.0 ± 3373.0 steps, p=0.287). There were no differences in sedentary (p=0.366), light (p=0.293), moderate (p=0.656) or vigorous (p=0.701) physical activity when average weeks were compared to one of imposed sedentary behavior. A greater number of SIT (4/8) participants had lower step counts during the imposed sedentary week, when compared to CON (1/8) participants. There was no difference (p>0.05) between CON and SIT groups for total calories consumed at any time-point. Caloric intake decreased significantly in the SIT group compared to the CON group (SIT = -27.9 ± 22.8%, CON = 10.0 ± 37.6%, p=0.028). More SIT (7/8) than CON (3/8) participants decreased caloric intake from baseline to 8 weeks (p>0.05). Conclusion: Physically active young adults did not alter physical activity profiles, but did decrease their caloric intake, in response to 8 weeks of imposed sedentary time. These findings may indicate a compensatory mechanism to imposed sitting in physically active adults.
Keywords: Nutrition; Physical activity; Imposed sedentary behavior; Riley County Research and Extension; Public health; Walk Kansas; Kinesiology (0575); Nutrition (0570); Public Health (0573)